ELECTRONIC TEXTBOOK - SUBJECT INFORMATIONEDUCATIONAL ENVIRONMENT OF INDEPENDENT WORK OF STUDENTS - Elena O. Ivanova (Russian State Vocational Pedagogical University, 2015)
The aim of the paper is to consider the characteristics of the electronic textbook as the subject of the information-educational environment, which ensures the unity both of the procedural and substantive aspects of training.Results. The evolution of views on the electronic textbook in the course of the expansion and awareness of the didactic potential of information and communication technologies is shown. The structure of the electronic textbook is presented in the paper. It includes the following modules: information (invariant content of education and the expansion of its variability); organizational and procedural (variable-based assignments aimed at acquiring information, as well as a means of reflection and evaluation of results); personal (information and telecommunication means of organizing own knowledge); communicative (the field of information and assessment of interaction); and pedagogical (monitoring cognitive activity of students). The structure has been developed with due regard to the need of independent work of a student with the content of education in information and educational environment.Scientific novelty. The features of the independent work of the student in terms of abundance of information through information and communication technologies are analyzed. Special attention is paid to the development of independent cognitive activity of students, their subject position in education. On this bases, the key position that should be considered during the development of the electronic textbook are specified: cognitive activity is considered as an active process of constructing students' new knowledge based on earlier formed personal experience; personal experience arises as a result of intellectual and cognitive activity of the student; cognition of something new requires an activity in the field of social communication; the efficiency of absorption of the content of education depends on the conditions of implementation of each student's value preferences, intellectual capabilities and features.Practical significance. The paper is provided with generalisation of existing visions of electronic textbooks. The research material can be useful both to implementers of such educational means, and the teachers mastering new forms of work with schoolchildren